(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the phenomenon of variability in the works by G. Smotrytskyj. Phonetical, morphological and lexical elements were analyzed. The reasons of language versatility were find out.